The Levels of Inhibitory Cytokines in the Serum of Patients with Hepatitis B and C - Ainor Rohmah; Sigit Setyawan; Tri Nugraha Susilawati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Hepatitis B and C Viruses (HBV dan HCV) can cause acute or chronic hepatitis that may develop into fibrosis, cirrhosis, and hepatocarcinoma. Previous studies have reported that hepatocyte damage is mainly due to overactive immune responses rather than viral infection. Cytokines are essential mediators in the immune response. This study aimed to determine the correlation between the levels of serum inhibitory cytokines, i.e., IL-4, IL-10, and TGF-Î², and the development of liver disease in patients with hepatitis B and C. The levels of serum IL-4, IL-10, and TGF-Î² from 58 patients with hepatitis B or hepatitis C were determined by ELISA. The progression of liver disease is inferred from the levels of serum transaminases and the degree of liver fibrosis. Data were analyzed using the Spearman correlation test with a p-value of < 0.05 is considered statistically significant. This study showed no correlation between the levels of serum IL-4, IL-10, and TGF-Î² and the development of liver disease in patients with hepatitis B and C (p > 0.05). Therefore, cytokine testing using ELISA was unable to replace liver biopsy to assess liver disease progression in patients with hepatitis B and C.